Expatriates' perception on factors affecting knowledge transfer between Asian expatriates and local employees - Zulkifly, Nurul Afiqah; Ismail, Maimunah; Hamzah, Siti Raba'ah; Yamato, Eriko; Muhammad Azlan Gan, Nur Nasuha Gan (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This paper aims to investigate the influence of individual factors (cultural intelligence and feedback seeking behavior) and social capital factors (shared vision and trust) on knowledge transfer between Asian expatriates and host country nationals (HCNs), as perceived by the former. This paper integrates the use of the Human Capital Theory, the Social Capital Theory, and the Anxiety and Uncertainty Management Theory to support the knowledge transfer framework between the two groups of human resources. Data were analyzed from a sample of 108 expatriates who are employed in multinational corporations and private companies in the area of Klang Valley, Malaysia. Results disclose that majority of these Asian expatriate are from South-East Asian and Far Eastern countries with a mean age of 39.6 years old, and have a moderate level of knowledge transfer and high levels of individual and social capital factors. Two factors were found as significant predictors of knowledge transfer, namely shared vision and cultural intelligence with a determination power of 23.6%.